1979
DOI: 10.1073/pnas.76.7.3523
|View full text |Cite
|
Sign up to set email alerts
|

Different rat-derived transforming retroviruses code for an immunologically related intracellular phosphoprotein.

Abstract: Kirsten sarcoma virus (Ki-MSV) and Harvey sarcoma virus (Ha-MSV) are mouse-rat recombinant viruses that were originally isolated by experimental inoculation of rats with helper-independent mouse type C viruses. We 75,[2972][2973][2974][2975][2976]. We report here that this new, purely rat sarcoma virus apparently codes for a p29, which shares immunological determinants and common V-8 protease-generated peptides with the p21 of Ha-MSV. The data suggest that the RaSV has acquired genetic information with simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
(13 reference statements)
2
32
0
Order By: Relevance
“…Thus, the p29 protein of Ra-SV appears to be a fusion protein analogous to the larger fusion proteins detected in a variety of other oncogenic retroviruses. The molecular structure of the genomic RNA of Ra-SV has not been elucidated, but rat 30S genes do not seem to be present in Ra-SV (52). This observation is consistent with our recent studies of Ha-SV, which showed that the p21-coding gene in Ha-SV is not comprised of rat 30S genetic sequences (15).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Thus, the p29 protein of Ra-SV appears to be a fusion protein analogous to the larger fusion proteins detected in a variety of other oncogenic retroviruses. The molecular structure of the genomic RNA of Ra-SV has not been elucidated, but rat 30S genes do not seem to be present in Ra-SV (52). This observation is consistent with our recent studies of Ha-SV, which showed that the p21-coding gene in Ha-SV is not comprised of rat 30S genetic sequences (15).…”
supporting
confidence: 86%
“…A surprising result was the observation that Ra-SV coded for a related protein, p29 (52). In this case, the src protein was a p21-like protein fused to a rat type C viral structural protein which appears to be a part of the gag precursor of rat type C viruses (H. Young, personal communication).…”
mentioning
confidence: 99%
“…Both RaSV-transformed cells and RaSV-induced fibrosarcomas in rats express a transforming protein of 29 kDa which has been designated p29 or v-Ra-Ras (56,57). An important characteristic of RaSV-induced transformation is that cells transformed with different isolates of RaSV derived from different rat tumors express the same or immunologically similar p29 proteins (57).…”
mentioning
confidence: 99%
“…Most acutely transforming retroviruses have been isolated following infection of animals with nontransforming replication-competent retroviruses, as was the case for the Harvey and Kirsten murine sarcoma viruses. However, acutely transforming viruses have also been generated in cultured cells using various nontransforming replication-competent retroviruses (15)(16)(17)23), showing that XMRV is not unique in this regard. Interestingly, production of acutely transforming viruses was facilitated by growth of the nontransforming parental viruses in chemically transformed cells or in cultured tumor cells (16,17).…”
mentioning
confidence: 99%